Infrared and Millimeter Waves, Conference Digest of the 2004 Joint 29th International Conference on 2004 and 12th International 2004
DOI: 10.1109/icimw.2004.1421950
|View full text |Cite
|
Sign up to set email alerts
|

Status of the Novosibirsk high power free electron laser

Abstract: A 100-MeV 8-turns accelerator-recuperator (AR) intended to drive a high-power infrared free electron laser (FEL) is under construction in Novosibirsk now. The FEL will provide up to 100 kW average power radiation in the wavelength range 2 -50 µm. As building up the full-scale machine takes a long time and much resources, it is reasonably to divide the project into two stages.The first-stage machine includes the AR with the fullscale RF-system and only one turn of electron beam, so the maximum energy of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…For the first time, gas breakdown (atmospheric pressure air) in the THz frequency range was carried out by radiation from a submillimeter laser [3]. In this paper, it was demonstrated that for λ = 385 and 359 µm, the breakdown power density is of the order of 1 MW cm −2 , which agrees well with the results in the infrared range (CO 2 [4], Nd [5], and ruby [6] lasers) from the point of view that the breakdown intensity increases as ω 2 . This scaling was also confirmed in a recent experiment in the Budker Institute for Nuclear Research, on a free-electron laser (FEL) [7,8].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…For the first time, gas breakdown (atmospheric pressure air) in the THz frequency range was carried out by radiation from a submillimeter laser [3]. In this paper, it was demonstrated that for λ = 385 and 359 µm, the breakdown power density is of the order of 1 MW cm −2 , which agrees well with the results in the infrared range (CO 2 [4], Nd [5], and ruby [6] lasers) from the point of view that the breakdown intensity increases as ω 2 . This scaling was also confirmed in a recent experiment in the Budker Institute for Nuclear Research, on a free-electron laser (FEL) [7,8].…”
Section: Introductionsupporting
confidence: 83%
“…The terahertz (THz) frequency range is the least studied frequency range from the point of view of gas discharge physics. Certain progress in the study of the discharge, sustained by the powerful radiation of the THz frequency range, was achieved due to the creation of powerful radiation sources in this band [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation characteristics of the Novosibirsk free electron laser (NFEL) [1] are gradually growing during the last year. The average output power reaches the value of 400 W (at 11.2 MHz) that corresponds to the peak power of about 1 Laser parameters For transmission of laser radiation from the accelerator hall to user stations, a 14-m optical beamline guiding terahertz radiation from the laser had been constructed.…”
Section: Introductionmentioning
confidence: 99%
“…The average output power reaches the value of 400 W (at 11.2 MHz) that corresponds to the peak power of about 1 Laser parameters For transmission of laser radiation from the accelerator hall to user stations, a 14-m optical beamline guiding terahertz radiation from the laser had been constructed. The beamline is separated from the accelerator vacuum with a 0.8-mm thick diamond window.…”
Section: Introductionmentioning
confidence: 99%